A Kaleckian approach to the financialization-distribution-inflation nexus: Germany and Austria in comparative perspective - Cara Dabrowski (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2025)
In this paper, I extend the Hein and Stockhammer model of distribution and inflation by incorporating structural trends of financialization through three Kaleckian channels: (1) sectoral recomposition, (2) financial overhead costs and rentiers' profit claims, and (3) the bargaining power of trade unions and workers. The model is calibrated to two scenarios that reflect the institutionalized fear experienced by workers under neoliberal income policies. Following a theoretical exploration of potential inflationary shocks, an empirical case study comparing Germany and Austria is conducted. The analysis validates the relevance of all three Kaleckian channels, though their individual strength varies. The findings indicate that while rising import prices triggered the initial inflationary shock, firms subsequently increased unit profits by keeping overall domestic prices high even though import prices decreased. An inflation decomposition suggests a more pronounced class conflict in Austria, potentially attributable to less severe labor market deregulation.
Keywords: D33; D43; E31; Q43; 330; Inflation; conflict inflation; distribution; Kaleckian theory of distribution; financedominated capitalism; financialization; financial and economic crisis